المنظمات الدولية والإقليمية وقصورها في حل الأزمات في ظل ثورات‎ الربيع العربي (ليبيا نموذج)‏ - حمد، عادل أدم (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
Throughout the ages, the world has known conflicts and tribulations that humanity has suffered and lived through, difficult periods in which the savagery of tyrants has erupted to destroy human beings, and to strike at the aspiration of all to establish peace and security, and to spread strife and cooperation for the happiness of creation. Despite the awakening and call for the exclusion of violence, and the focus on wisdom to resolve all conflicts, and the initiatives that have taken various forms over time from appeals, declarations, consensus and organization, we are still looking after the period of time after the outbreak of wars and conflicts and the partiesinvolved in fighting indifferent to what was agreed They forget their commitment. A more focused view is that international organizations, and more specifically international intergovernmental organizations,have played the most prominent role in the international and regional arena as institutions working to resolve conflicts. The issue of solving international problems and conflicts is one of the main reasons for the establishment of international and regional organizations. Libya faces many regional and international challenges and crises, including the spread of militias ,the dispersal of people into groups and the spread of vengeance and hatred. There is no doubt that these militias are confronted and supported by external forcesand follow the agenda of other Libyan. There is no point in any dialogue, conferences or agreements unless there is a force and an army on the ground, and this will only be done by eliminating these militias and internal conflicts, uniting the ranks and the world and leaving the differences. It was rather that the Arab League has one position and the Arab countries as well the direction of the current conflict and the creation of moderate political solutions to solve the crisis, rather than differences and support of all conflicting parties to divide the row and ignite the wars.